CONCREWALL - Lagad Shrinivas,; Lashkar Akash,; Gawali Navnath,; Ransing Aniket,; Nanaware Rushikesh,; Dr. Gunaware P.D,; Prof. Pachpute A. B, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This paper proposes the study of a method to implement a new technique regarding using polystyrenein construction of structure wall for housing which includes not only construction of bungalow but also building upto four floors as well as row houses whichever is necessary. This technique comes handy since polystyrene panels which contains two set of galvanizing welded mesh where vertical mesh forming waves result in creating reinforced concrete micropillars once the panel is coated with concrete (this technique has been used successfully to reinforce historic or artistic buildings). It is a system which is used to construct storey upto G+3 with single panel and multiple storey with double panel but it is yet to be tested according to Building Codes.
Keywords: Polystyrenein; Concrewall; Building Codes; Cement; Sand; Bricks; Siporex; Polystyrene Wall